The Importance of Quality of Work-Life on Teacher Organizational Citizenship Behavior: Consequences of Leader-Member Exchange and Organizational Commitment - Darwin, Darwin; Sofiyan, Sofiyan; Astiti, Ni Made Ayu Gemuh Rasa; Lina, Ni Putu Maha; Sudirman, Acai (FKIP Universitas Lampung, 2022)
The Importance of Quality of Work Life on Teacher Organizational Citizenship Behavior: Consequences of Leader-Member Exchange and Organizational Commitment. Objective: The study's major goal was to look at the quality of work life, leader member exchange, and organizational commitment to organizational citizenship behavior of private high school instructors in Pematangsiantar City. Methods: This study employs a quantitative research strategy. Multiple regression testing, hypothesis testing using simultaneous and partial approaches, and correlation testing with the coefficient of determination are all used in data analysis. Findings: The results of this research explain that quality of work life, leader member exchange, and organizational commitment have a positive and significant effect on organizational citizenship behavior. Conclusion: The findings of this study confirm the quality of work life and leader member exchange for schools and for teachers is for schools to attract and maintain the work spirit of teachers. Furthermore, there is a strong organizational commitment within the individual, causing teacher OCB to run optimally.Keywords: quality of work life,leader-member exchange,organizational commitment, organizational citizenship behavior.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202201